The maximum standardized FDG uptake on PET-CT in patients with non-small cell lung cancer - Ozgul, Mehmet Akif; Kirkil, Gamze; Seyhan, Ekrem Cengiz; Cetinkaya, Erdogan; Ozgul, Guler; Yuksel, Mahmut (Pagepress Publ, 2013)
Background: Non-small cell lung cancer (NSCLC) accounts for approximately 80% of new diagnoses of pulmonary carcinoma. This study investigated the correlation between 18 F-fluorodeoxyglucose uptake in computerized tomography integrated positron emission tomography and tumor size, lymph node metastasis, and distant metastasis in patients with NSCLC. Methods: The records of 151 NSCLC patients (139 male, 12 female; mean age 59.60 years) were evaluated retrospectively. Results: Forty-one cases were adenocarcinomas; 45 squamous cell carcinomas; and 65 unspecified NSCLC. When the cases were categorized according to tumor size (group 1, <= 3 cm; group 2, > 3 and >= 5 cm; group 3, > 5 cm), the maximum standardized uptake value (SUVmax) was significantly lower in groups 1 and 2 compared with group 3 (p = 0.006 for each). Considering all cases, tumor SUVmax was not correlated with age, gender, or histopathological type. Lymph node metastases were pathologically proven in 24 cases: 24% of these were adenocarcinomas, 6% squamous cell carcinomas, and 16% unspecified NSCLC. Neither lymph node involvement nor distant metastases were correlated with tumor SUVmax, although lymph node size was positively correlated with lymph node SUVmax (r = 0.775; p < 0.001). Conclusions: SUVmax was significantly associated with tumor size, but not with distant metastases or lymph node involvement. Therefore, SUVmax on positron emission tomography is not predictive of the presence of metastases.
Keywords: Non-small cell lung cancer; Positron emission tomography; Standardized uptake value